My Story with Pathways to Education/Passeport pour ma réussite: A Game Changer in my School and Personal Journey - Lafond, Thomas; Cabezas, Alejandra (Apprendre et enseigner aujourd’hui, 2025)
Pathways to Education/Passeport pour ma réussite is a national, charitable organization breaking the cycle of poverty through education. The award-winning Pathways Program creates positive social change by supporting youth living in low-income communities to overcome barriers to education, graduate from high school, and build the foundation for a successful future. Through the collective power of partnerships, Pathways to Education’s innovative program is preparing youth for tomorrow. Throughout his high school years, Thomas Lafond benefited from the organization’s services. He shares with us the impact of the support he received on his own path.